Maintenance of sexual activity following androgen deprivation in males. (September 2020) - Duthie, Cassian J.; Calich, Hannah J.; Rapsey, Charlene M.; Wibowo, Erik
Abstract: Androgen deprivation therapy (ADT) is a common treatment for men with systemic prostate cancer. However, ADT leads to sexual dysfunction, causing >80 % of couples to cease sexual activity completely. Here, we use a biopsychosocial framework to review factors that may influence the ability of patients on ADT to remain sexually active. We address sexual factors prior to ADT, neurobiological factors, intermittent ADT, sex aids, exercise, sleep, partner factors, masculinity, non-penetrative intimacy, depressive symptoms, and access to counselling or patient education programs. We make suggestions for future research in order to extend our understanding in this field with the goal of improving evidence-based treatment protocols and practice. Importantly, we suggest that clinicians should discuss options for sexual intimacy after ADT with both patients and their partners, as sexual inactivity is not inevitable for most, and strategies are available for helping maintain sexual intimacy.